2015
DOI: 10.1128/jb.00019-15
|View full text |Cite
|
Sign up to set email alerts
|

Two-Tiered Histidine Kinase Pathway Involved in Heat Shock and Salt Sensing in the General Stress Response of Sphingomonas melonis Fr1

Abstract: The general stress response (GSR) allows bacteria to monitor and defend against a broad set of unrelated, adverse environmental conditions. In Alphaproteobacteria, the key step in GSR activation is phosphorylation of the response regulator PhyR. In Sphingomonas melonis Fr1, seven PhyR-activating kinases (Paks), PakA to PakG, are thought to directly phosphorylate PhyR under different stress conditions, but the nature of the activating signals remains obscure. PakF, a major sensor of NaCl and heat shock, lacks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The shared ExxHRxxN motif at the site of histidine phosphorylation (41, 66) has led to the collective moniker HRxxN kinases to represent these two groups (64, 65). The HWE superfamily, Cl06527 (previously called the HisKA_2 superfamily), also encompasses these related DHp domains (29).…”
Section: Organization Of the General Stress Response Chromosomal Locumentioning
confidence: 99%
See 2 more Smart Citations
“…The shared ExxHRxxN motif at the site of histidine phosphorylation (41, 66) has led to the collective moniker HRxxN kinases to represent these two groups (64, 65). The HWE superfamily, Cl06527 (previously called the HisKA_2 superfamily), also encompasses these related DHp domains (29).…”
Section: Organization Of the General Stress Response Chromosomal Locumentioning
confidence: 99%
“…Some GSR kinases possess N-terminal two-component REC domains, which permit integration of signals from other sensory kinase(s). An example is the PhyR kinase PakF, which is activated by phosphorylation of its N-terminal receiver domain by the HisKA-family kinase KipF (65). Finally, some HisKA_2 family kinases such as S. melonis PakG lack signal input domains altogether (64).…”
Section: Regulatory Kinases: Signaling Complexity In General Stress Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, all histidine kinases demonstrated to phosphorylate PhyR and/or regulate GSR transcription to date are HWE/HisKA2 kinases [7,911,3640]. The only histidine kinase known to signal to the GSR pathway that is not HWE/HisKA2 does so indirectly via an HWE/HisKA2 kinase that directly phosphorylates PhyR [9,41]. …”
Section: Phylogenetic Distribution and Functionmentioning
confidence: 99%
“…Studies of GSR regulation in Alphaproteobacteria have also revealed an important role for SDRRs, which interact biochemically and/or genetically with HWE/HisKA2 kinases to modulate GSR transcription [7,9,36,4143]. Though the mechanistic basis by which SDRRs execute this function remains undefined, they have been hypothesized to function as allosteric regulators of HWE/HisKA2, competitive kinase inhibitors, phospho-sinks, or as components of parallel regulatory pathways.…”
Section: Phylogenetic Distribution and Functionmentioning
confidence: 99%